The elements of the compact city on sustainable urban development In Petaling Jaya, Selangor, Malaysia - Nor’Azmi, Syima Zayanah; Sahrir, Syazwani (Malaysian Institute of Planners, 2024)
Urbanization is an ongoing global phenomenon that demands innovative approaches to balance economic growth with environmental sustainability. This study investigates the elements contributing to the development of a compact city and their impact on sustainable urban development in the context of Petaling Jaya, Selangor. The study aims to identify the elements of compact cities that contribute to sustainable urban development in Petaling Jaya and explore the elements that contribute to sustainable urban development in Petaling Jaya. The research employs a qualitative approach, combining interviews with experts and document analysis of compact cities. Through thematic analysis, the study identifies the core elements of compact cities in Petaling Jaya, exploring their influence on sustainability. Preliminary findings reveal that the compact city is shaped by population density, mixed land use, and transportation infrastructure. Stakeholder perspectives shed light on these compact city elements' perceived benefits and challenges. Additionally, the document analysis examines the elements of the compact city that may influence sustainable urban development. This study contributes to the existing body of knowledge by providing a nuanced understanding of the elements contributing to the compact city characteristics and their role in fostering sustainable urban development.